Peningkatan Peran Antenatal Care (ANC) dan Pemanfaatan TOGA dalam Kehamilan di Puskesmas Sawangan Depok - Erna Harfiani; Muttia Amalia; Aulia Chairani (Universitas Mathla'ul Anwar Banten, 2019)
ENHANCING OF ANC AND UTILIZATION OF TOGA IN PREGNANCY AT SAWANGAN DEPOK. Women’s and children’s health problems today remain a global challenge and need remedial action. Maternal death is the death of a woman during pregnancy or death within 42 days of termination of pregnancy. Antenatal care (ANC) is an attempt to prevent the causes of morbidity and mortality in pregnant women and children. During pregnancy various physiological changes occur in pregnant women, this certainly has an impact on the psychology and health of pregnant women. TOGA (Family medicinal plants) can be used to help overcome this uncomfortable situation. Plants that can be used by pregnant women include, such as ginger, red spinach, red betel, green betel, tomatoes, and broccoli. There is a possibility of abnormalities such as bleeding, preeclampsia, and infection during pregnancy. Therefore there is a need for monitoring in the form of Antenatal Care during pregnancy and the mother’s understanding of early detection of the risk of abnormalities during pregnancy. This community service is carried out to increase community knowledge around the Sawangan Depok Community Health Center about the importance of ANC and the use of TOGA in pregnant women as well as training in the introduction of several abnormalities and emergencies during pregnancy through counseling with lecture media, pamphlets and pocketbooks on ANC and the use of TOGA. This activity went well and the results can be seen there is an increase in the results of the posttest compared to the pretest, and statistically, there are significant differences.